Sensor Signal and Information Processing III - Woo, Wai Lok; Gao, Bin (Sensors (Basel, Switzerland), 2020)
[...]the preliminary estimation with the dynamical model of the receiver’s motion are used to obtain the final estimation. In a similar development, Kim and Kudo [12] have proposed a new class of nonlocal Total Variation (TV), in which the first derivative and the second derivative are mixed. Since most existing TV only considers the first-order derivative, it suffers from problems such as staircase artifacts and loss in smooth intensity changes for textures and low-contrast objects, which is a major limitation in improving image quality. [...]an improved modality independent neighborhood descriptor (MIND) based on the foveated nonlocal self-similarity is designed for effective structural representations. [...]the accurate and efficient 3D medical image registration is realized by minimizing the similarity measure-based MRF energy function.